Efficient logistics : a key to Vietnam's competitiveness - Blancas, Luis C. (Directions in development (Washington, D.C.). Countries and regions., 2014)
"Vietnam has achieved sustained economic growth, primarily driven by a rapidly expanding labor force and a shift in economic activity away from low-productivity subsistence agriculture toward the higher-productivity manufacturing and services sectors. However, the country's socioeconomic success is now facing both short- and long-term challenges. Over the longer term, Vietnam is faced with the challenge that its main drivers of past growth are being depleted and need to be replaced by intra-sectoral productivity improvements. More efficient transport and logistics can play a significant role in increasing productivity. Competitiveness enhancements can better position Vietnam to benefit from global demand, to better serve domestic markets, to attract investment, and to generate quality jobs. This publication highlights opportunities to make freight itineraries more reliable, to make roads safer and more conducive to high-volume commercial use, to increase port sector efficiencies, and to better integrate barges, trucks, warehouses, and gateways. It also proposes interventions and policies that can address both short-term and long-term challenges. This work is divided into four detailed chapters: 1) overview, 2) Vietnam's current situation, 3) freight stakeholder challenges and opportunities, and 4) issues screening and list of actionable recommendations."--